Learning English Through Hobbies: Exploring Students’ Learning Style at English Skills Classes - Dayanti, Gista Rahma; Ifani, Muhammad Zulfi; Maulana, Mahesa; Ratih, Koesoemo (Universitas Muhammadiyah Surakarta, 2023)
This study delves into the expanding differences and diversities among students in higher education, encompassing various backgrounds, ethnicities, cultures, and learning styles. The advent of technological advancements has prompted educators to reevaluate traditional teaching approaches, emphasizing the importance of aligning teaching methods with students' learning styles to prevent dissonance. Misalignment between teaching and learning styles can lead to student dissatisfaction and poor performance. This paper explores the significance of learning styles in achieving successful education outcomes. It investigates how individual learning styles, such as visual, auditory, and kinesthetic, impact language learning success, particularly in English education. The study examines the correlation between learning styles, hobbies, and language acquisition techniques. The results indicate that incorporating hobbies into learning can enhance students' comfort and receptiveness to the educational process, thereby promoting language skills development.